An Experimental Journey with Self-Made Online Courses: How does it differ? - D., Anitha; C., Jeyamala; S.J., Thiruvengadam; S, Saravana Perumaal (Journal of Engineering Education Transformations, 2025)
An effective learner centric environment that creates opportunities for interdisciplinary learning and skill development on recent technologies with self-learning capability has been the prime focus of present education. With the limited infrastructure and teaching faculty, it is not always possible to give multiple learning opportunities to students. Massive Open Online Courses (MOOC) have been a boon to the students for developing their knowledge and skills. There are number of national and international MOOC platforms providing various courses offered by different institutions under a learning framework that may differ with different platforms. Though the students gain knowledge through these platforms, they lack the important elements of learning: Personal interaction and motivation by the instructors. This leads to more drop-outs from the courses offered in these platforms. With the intention of providing the personal interaction and motivation, the institution has developed online courses in the trending domain areas under the new initiatives of the academic process of our institution. Eleven online courses have been developed to promote interdisciplinary knowledge relevant to the engineering curriculum and are currently offered to the students of our institution. This paper presents the experience in the design of these online courses and analyses the performance of the learners in enhancing the skill development in the state-of-the-art technologies. There is a need of understanding whether these self-made online courses make a difference when compared to other MOOC platforms. The student feedback, both quantitative and qualitative, and the performance scores have been analyzed for the same. The observed results are encouraging to proceed with this new initiative.